Do nursing stations within bays of hospital wards reduce the rate of inpatient falls? – An Interrupted Time Series Analysis from the United Kingdom - Ali, U; Judge, A; Foster, C; Brooke, A; Davis, L; James, K; Marriott, T; Lamb, S (Royal Statistical Society, 2017)
Falls are a major public health burden for individuals and society. Falls are associated with loss of independence, functional decline and are a contributing reason for subsequent admission to long-term care. The financial burden associated with injurious falls is substantial. This study aims to evaluate whether the introduction of portable nursing stations within bays of hospital wards, has led to a change in trend of the monthly rate of inpatient falls.